Demo: Experimenting software radio with the Sora platform - Zhang, Jiansong; Tan, Kun; Xiang, Sen; Luo, Qi; He, Yong; Fang, Ji; Zhang, Yongguang; Yin, Qiufeng (Sigcomm 10 Demo Abstract, 2010)
Sora is a fully programmable, high performance software radio platform based on commodity general-purpose PC. In this demonstration, we illustrate the main features of the Sora platform that provide researchers flexible and powerful means to conduct wireless experiments at different levels with various goals. Specifically, the demonstrator will show four useful applications for wireless research that are built based on the Sora platform: 1) A capture tool that allows one to take a snapshot on a wireless channel; 2) a signal generation tool that allows one to transmit arbitrary baseband wave-form over the air, from a monophonic tone to a complex modulated frame; 3) an on-line real-time receiving application that uses the Sora User-Mode Extension; and 4) a fully featured Software radio WiFi driver (SoftWiFi) that can seamlessly inter-operate with commercial WiFi cards.